A prototype of an automatic mattress turning device: a study of interface pressure at bony prominences in normal subjects - Kanyaluck Uttarachon (2019)
© 2019, Khon Kaen University,Research and Technology Transfer Affairs Division. All Right Reserved. This study was to test an interface pressure at bony prominences when using a prototype of an automatic mattress turning device (AMTD) to reposition a body while lying in a hospital bed. The AMTD consists of a set of air bellows (two large in the middle and two lateral small ones) placed under a 4 inches foam mattress and microcontrollers with air pumps and solenoid valves controlling inflation and deflation of each air bellow. After inflation, it lifted one side of the mattress up so that a body on the mattress turned from supine to a 30° lateral tilt position. Using an XSENSOR pressure mapping system, peak pressure was recorded (mmHg) and peak pressure indexes (PPIs) (mmHg/cm2) over bony prominences of the body of 20 normal volunteers were calculated and compared between the supine and the 30° lateral tilt positions. In the 30° lateral tilt position, the mean peak pressure reduced significantly at the occiput (30.75, 27.26, p = 0.003), the sacroccygeal area (35.99, 27.26, p < 0.001) whereas the mean PPIs also reduced significantly at the occiput (21.53 to 14.93, p < 0.001), the scapula (21.65 to 18.78, p 0.011), and the sacrococygeal area (33.76 to 27.53, p = 0.001). The peak pressure and the PPI were highest at sacrococcygeal area in supine and decreased significantly when a body was turned to a 30° lateral tilt with this automatic mattress turning device.